The relationship between satisfaction on hygiene and motivator, work overload and job performance among private college and university lecturers in Kota Kinabalu, Sabah - Yong, Tink Tink (2011)
This study aims to find out the relationship satisfaction on hygiene-motivator, work overload and job performance among private college and university lecturers in Kota Kinabalu. The objectives of this study. were achieved by examining the relationship between job performance (dependent variable) and two factors identified as independent variables which include satisfaction on hygiene and motivator and work overload. Results from the questionnaire collected from 116 respondents were analyzed using the multiple regression analysis. The analysis revealed that all independent variables (satisfaction on hygiene-motivator and work overload) have the significant relationship with job performance among private college and university lecturers. For the moderator test using hierarchical multiple regression, the result shows that gender and position level didn't moderate the job performance through independent variables. Although the relationship between dependent variable and independent variables when regressed together produced an acceptable result, further research should be done in order for this model to be proposed as a general model for developing a framework that can explain the job performance among college and university lecturers.